Electrode active material, electrode mixture, and battery

By integrating a diamond-type silicon crystal phase with a specific 5-membered ring size range into silicon clathrate II electrode active materials, the battery's volume change issue is mitigated, improving electrode durability and performance.

JP2025058598AActive Publication Date: 2025-04-09TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023168624
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Silicon (Si) electrode active materials in batteries experience large volume changes during charging and discharging, leading to deterioration of electrode function with repeated cycles.

Method used

Incorporating a small crystal phase of diamond-type silicon alongside the silicon clathrate II crystal phase, with a specific 5-membered ring size range of 3.752 Å to 3.780 Å, to suppress volume changes during charge and discharge.

Benefits of technology

The proposed solution effectively reduces the volume change due to charge and discharge, thereby enhancing the durability and performance of the electrode active material in batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058598000001_ABST
    Figure 2025058598000001_ABST
Patent Text Reader

Abstract

To provide an electrode active material that undergoes small volumetric change upon charging and discharging.SOLUTION: The present disclosure provides an electrode active material having a silicon clathrate II type crystal phase, in which the five-membered ring size in the crystal phase is 3.752Å or more and 3.780Å or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode active material, an electrode mixture, and a battery. [Background technology]

[0002] In recent years, the development of batteries has been actively carried out. For example, in the automobile industry, development of batteries for use in electric vehicles (BEVs), plug-in hybrid vehicles (PHEVs), or hybrid electric vehicles (HEVs) is underway. In addition, Si (silicon) is known as an electrode active material used in batteries. For example, Patent Document 1 discloses an electrode active material having a silicon clathrate II type crystal phase and having voids inside the primary particles. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-158004 Summary of the Invention [Problem to be solved by the invention]

[0004] Silicon has a large theoretical capacity and is effective in increasing the energy density of batteries. On the other hand, silicon undergoes large volume changes during charging and discharging. Large volume changes during charging and discharging can lead to problems such as a decrease in the function of the electrode active material when the battery is repeatedly charged and discharged.

[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode active material that undergoes small volume change upon charging and discharging. [Means for solving the problem]

[0006] In order to solve the above problems, the present inventors have conducted extensive research and have found that when an electrode active material has a small amount of diamond-type silicon crystal phase in addition to a silicon clathrate II crystal phase, the volume change during charging and discharging is suppressed. At the same time, the present inventors have found that even if the proportion of diamond-type silicon crystal phase in an electrode active material is the same, there is a difference in the volume change during charging and discharging. When the present inventors have examined the cause of the difference in detail, they have found that the five-membered ring size of the silicon clathrate II crystal phase has a large effect on the volume change during charging and discharging, and have completed the following invention.

[0007] [1] An electrode active material having a silicon clathrate II type crystalline phase, The electrode active material, wherein the five-membered ring size in the crystal phase is 3.752 Å or more and 3.780 Å or less.

[0008] [2] The above-mentioned electrode active material has voids inside the primary particles. [1] An electrode active material.

[0009] [3] An electrode mixture comprising the electrode active material according to [1] or [2] and at least one of a conductive material and a binder.

[0010] [4] A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, The battery, wherein the positive electrode layer or the negative electrode layer contains the electrode mixture according to [3].

[0011] [5] The battery according to [4], wherein the electrolyte layer contains a solid electrolyte. Effect of the Invention

[0012] The present disclosure has an effect of providing an electrode active material that undergoes small volumetric change upon charging and discharging. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic perspective view illustrating a crystalline phase of Si. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 3] 1 shows the results of the volume expansion rate of batteries using the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The electrode active material, electrode mixture, and battery according to the present disclosure will be described in detail below.

[0015] A. Electrode active material The electrode active material in the present disclosure has a silicon clathrate II crystal phase. Furthermore, the five-membered ring size of the silicon clathrate II crystal phase is usually 3.752 Å or more and 3.780 Å or less.

[0016] According to the present disclosure, since the size of the five-membered ring of the silicon clathrate II crystal phase is within a predetermined range, the electrode active material has a small volume change due to charging and discharging. As described above, Si has a large theoretical capacity and is effective in increasing the energy density of a battery. On the other hand, Si has a large volume change during charging and discharging. If the volume change during charging and discharging is large, there is a problem that the function of the electrode active material is easily deteriorated when charging and discharging are repeated. In response to such a problem, the present inventors have conducted extensive research and have found that when the electrode active material has a small amount of diamond-type silicon crystal phase in addition to the silicon clathrate II crystal phase, the volume change during charging and discharging is suppressed.

[0017] At the same time, the inventors have found that even if the proportion of diamond-type silicon crystal phase in the electrode active material is the same, there is a difference in the volume change during charging and discharging. That is, the inventors have found that there is a phenomenon that cannot be explained only by the proportion of diamond-type silicon crystal phase. Therefore, the inventors have studied in detail the cause of the above difference and found that the five-membered ring size of the silicon clathrate II crystal phase has a large effect on the volume change during charging and discharging.

[0018] Specifically, the inventors have found that the volume change during charging and discharging can be suppressed by adjusting the size of the five-membered ring in the crystal phase of silicon clathrate type II to a predetermined range. It is speculated that the reason why the volume change can be suppressed is that the insertion and desorption of Li via the five-membered ring becomes smooth by adjusting the size of the five-membered ring to a predetermined range. On the other hand, it is speculated that if the size of the five-membered ring is too large or too small, the five-membered ring itself is distorted, or the six-membered ring adjacent to the five-membered ring is distorted, and therefore the volume change due to charging and discharging cannot be suppressed.

[0019] In addition, the electrode active material in the present disclosure has a silicon clathrate II type crystal phase. As shown in FIG. 1(a), in the silicon clathrate II type crystal phase, a polyhedron (cage) including a pentagon (five-membered ring) or a hexagon (six-membered ring) is formed by a plurality of Si elements. This polyhedron has a space inside that can contain metal ions such as Li ions. By inserting metal ions into this space, the volume change due to charging and discharging can be suppressed. In particular, in an all-solid-state battery, in order to suppress the volume change due to charging and discharging, it is generally necessary to apply a high confining pressure, but by using the electrode active material in the present disclosure, the confining pressure can be reduced, and as a result, the size of the confining jig can be suppressed. On the other hand, as shown in FIG. 1(b), in the diamond-type silicon crystal phase, a tetrahedron is formed by a plurality of Si elements. Since the tetrahedron does not have a space inside that can contain metal ions such as Li ions, the diamond-type silicon crystal phase is less likely to suppress the volume change due to charging and discharging than the silicon clathrate II type crystal phase. However, if the electrode active material contains a small amount of diamond-type silicon crystal phase, the volume change due to charging and discharging can be suppressed in some cases.

[0020] The electrode active material in the present disclosure has a silicon clathrate II type crystal phase. The five-membered ring size of the silicon clathrate II type crystal phase is usually 3.752 Å or more and 3.780 Å or less, and may be 3.755 Å or more and 3.775 Å or less. When the five-membered ring size is within a predetermined range, the electrode active material has a small volume change due to charging and discharging. The five-membered ring size is obtained by performing Rietveld analysis on the XRD measurement results, creating a crystal model based on the atomic position information, and calculating the distance between each atom in the crystal model. Specifically, the maximum value of the diagonal length of the five-membered ring is the five-membered ring size.

[0021] The electrode active material in the present disclosure preferably has a silicon clathrate II type crystalline phase as a main phase. The term "main phase" means that the peak belonging to the crystalline phase has the highest diffraction intensity among the peaks observed in X-ray diffraction measurement. The proportion of the silicon clathrate II type crystalline phase contained in the electrode active material is, for example, 80% by weight or more, may be 85% by weight or more, may be 90% by weight or more, or may be 95% by weight or more. The proportion of the silicon clathrate II type crystalline phase contained in the electrode active material may be 100% by weight or less than 100% by weight. The proportion of the crystalline phase can be obtained by performing Rietveld analysis on the XRD measurement results and using the analysis results and the RIR method (Reference Intensity Ratio method).

[0022] The electrode active material in the present disclosure may or may not have a crystalline phase of silicon clathrate type I. "Having no crystalline phase" means that no peak of the crystalline phase is confirmed in X-ray diffraction measurement.

[0023] The electrode active material in the present disclosure may or may not have a diamond-type silicon crystalline phase. The proportion of the diamond-type silicon crystalline phase contained in the electrode active material may be, for example, 0% by weight, or more than 0% by weight, or 0.2% by weight or more. On the other hand, the proportion of the diamond-type silicon crystalline phase contained in the electrode active material may be, for example, 5% by weight or less, or 3% by weight or less.

[0024] The composition of the electrode active material in the present disclosure is not particularly limited, but may include Na x S 136 It is preferable that the composition is represented by (0≦x≦24). x may be 0 or may be greater than 0. On the other hand, x may be 20 or less, 10 or less, or 5 or less. The composition of the electrode active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry.

[0025] The electrode active material in the present disclosure may be a primary particle, or a secondary particle formed by aggregation of the primary particles. 50 ) is not particularly limited, but may be, for example, 0.1 μm or more and 50 μm or less, or 0.5 μm or more and 30 μm or less. 50 ) can be calculated, for example, from measurements using a scanning electron microscope (SEM).

[0026] The electrode active material preferably has voids inside the primary particles. The porosity is, for example, 4% or more, and may be 10% or more. The porosity is, for example, 40% or less, and may be 20% or less. The porosity can be determined, for example, by the following procedure. First, a cross section of an electrode layer containing an electrode active material is taken by ion milling. The cross section is then observed with a SEM (scanning electron microscope) to obtain a photograph of the particles. From the obtained photograph, silicon parts and void parts are clearly distinguished using image analysis software, and the image is binarized. The areas of the silicon parts and void parts are determined, and the porosity (%) is calculated from the following formula. Porosity (%) = 100 × (area of ​​void part) / ((area of ​​silicon part) + (area of ​​void part))

[0027] The electrode active material in the present disclosure is generally used in a battery. The electrode active material in the present disclosure may be a negative electrode active material or a positive electrode active material, but the former is preferred.

[0028] The method for producing the electrode active material is not particularly limited, but preferably includes an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy, and a firing step of calcining the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type II crystal phase.

[0029] The alloying step is a step of reacting a Na source and a Si source to obtain a Na-Si alloy. The Si source is, for example, simple Si. The Si source is preferably porous Si having many voids inside the primary particles. On the other hand, the Na source contains at least Na. Examples of the Na source include metallic Na, NaH, and metallic Na dispersions in which metallic Na particles are dispersed in oil.

[0030] A method of obtaining a Na-Si alloy by reacting a Na source and a Si source includes, for example, a method of heating a mixture containing a Na source and a Si source. The heating temperature is, for example, 300°C or higher, may be 310°C or higher, may be 320°C or higher, or may be 340°C or higher. On the other hand, the heating temperature is, for example, 800°C or lower, may be 600°C or lower, or may be 450°C or lower.

[0031] The Na-Si alloy preferably has a Zintl phase, and more preferably has the Zintl phase as the main phase. The composition of the Na-Si alloy is not particularly limited, but may be Na z S 136 It is preferable that the composition be represented by (121≦z≦151).

[0032] The firing step is a step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate II type crystal phase. In the firing step, it is preferable to adjust the firing conditions so that the five-membered ring size of the silicon clathrate II type crystal phase is 3.752 Å or more and 3.780 Å or less.

[0033] The five-membered ring size may be correlated with the crystallite size of the silicon clathrate II crystal phase. The crystallite size can be controlled by adjusting the sintering conditions. Specifically, the crystallite size can be adjusted by considering the balance between nucleation and nucleation growth during sintering. The balance between nucleation and nucleation growth during sintering can be controlled, for example, by the sintering temperature. Here, in order to form the silicon clathrate II crystal phase from the zintl phase contained in the Na-Si alloy, sintering at a relatively high temperature is required. Specifically, the Na-Si alloy needs to be sintered at a temperature of 340°C or higher. On the other hand, when sintering is performed at a temperature of 340°C or higher, the nucleation growth of the silicon clathrate II crystal phase takes precedence over the nucleation of the silicon clathrate II crystal phase, so the crystallite size of the silicon clathrate II crystal phase tends to become large. As a result, the five-membered ring size also tends to become large.

[0034] In contrast, by firing at a temperature below 340°C before firing at a temperature of 340°C or higher, nucleation takes precedence over nucleation growth, and the crystallite size can be reduced. As a result, the 5-membered ring size also tends to be small. In other words, the firing process preferably includes at least a first firing process in which the Na-Si alloy is fired at a temperature below 340°C, and a second firing process in which the compound that has been subjected to the first firing process is fired at a temperature of 340°C or higher.

[0035] The first firing process is a process in which the Na-Si alloy is fired at a temperature of less than 340°C. In the first firing process, a scavenger, which will be described later, may or may not be used. The firing temperature in the first firing process is usually less than 340°C, may be less than 310°C, or may be 300°C or less. On the other hand, the firing temperature in the first firing process is, for example, 250°C or more, may be 270°C or more, or may be 280°C or more. The firing time in the first firing process is, for example, 1 hour or more and 50 hours or less, or may be 5 hours or more and 30 hours or less.

[0036] The second baking treatment is a treatment in which the compound that has been subjected to the first baking treatment is baked at a temperature of 340°C or higher. In the second baking treatment, it is preferable to use a scavenger described later, and among them, it is preferable to use AlF3. The baking temperature in the second baking treatment is usually 340°C or higher, and may be 360°C or higher. On the other hand, the baking temperature in the second baking treatment may be, for example, 450°C or lower. The baking time in the second baking treatment is, for example, 1 hour or more and 120 hours or less, and may be 10 hours or more and 80 hours or less. It is preferable that the compound that has been subjected to the second baking treatment has a silicon clathrate II type crystal phase.

[0037] The calcination step may include a third calcination step in which the compound subjected to the second calcination step is calcined at a temperature of 340° C. or higher. In the third calcination step, it is preferable to use a scavenger described later, and it is particularly preferable to use ZnCl2. The calcination temperature in the third calcination step is usually 340° C. or higher, and may be 360° C. or higher. On the other hand, the calcination temperature in the third calcination step may be, for example, 450° C. or lower. The calcination time in the third calcination step is, for example, 1 hour or more and 120 hours or less, and may be 10 hours or more and 80 hours or less. It is preferable that the compound subjected to the third calcination step has a silicon clathrate II type crystal phase as a main phase.

[0038] In the firing step, it is preferable to use a scavenger that captures Na in the Na-Si alloy. One example of the scavenger is a Na getter agent that reacts with Na vapor generated from the Na-Si alloy. The Na getter agent is disposed, for example, in a state where it is not in contact with the Na-Si alloy. Examples of the Na getter agent include SiO, MoO3, FeO, and Fe3O4. When using a Na getter agent, it is preferable to perform the firing step in a reduced pressure atmosphere.

[0039] Another example of the scavenger is a Na trapping agent that directly reacts with the Na-Si alloy to receive Na. The Na trapping agent is, for example, arranged in contact with the Na-Si alloy. Examples of the Na trapping agent include CaCl2, AlF3, CaBr2, CaI2, Fe3O4, FeO, MgCl2, ZnO, ZnCl2, and MnCl2. When using a Na trapping agent, the firing process may be performed in a reduced pressure atmosphere or in a normal pressure atmosphere.

[0040] In addition, the balance between nucleation and nucleus growth during firing can be controlled, for example, by the type, particle size, and amount of the scavenger. For example, by reducing the particle size of the Na trapping agent, which is the scavenger, the contact area between the Na trapping agent and the Na-Si alloy increases. This makes it easier for Na to be extracted from the Na-Si alloy, and nucleation takes precedence over nucleus growth, allowing the crystallite size to be adjusted to be small. On the other hand, it is estimated that if the contact area between the Na trapping agent and the Na-Si alloy increases too much, the diamond-type silicon crystal phase, which is more stable than the silicon clathrate II crystal phase, is more likely to be generated.

[0041] B. Electrode composite material The electrode mixture in the present disclosure contains the above-mentioned electrode active material, and at least one of a conductive material and a binder.

[0042] According to the present disclosure, by using the above-mentioned electrode active material, an electrode mixture that undergoes small volume change upon charging and discharging is obtained.

[0043] The electrode mixture contains an electrode active material and at least one of a conductive material and a binder. The electrode active material is the same as that described in "A. Electrode Active Material" above. The electrode active material may be a negative electrode active material or a positive electrode active material, but the former is preferred. That is, the electrode mixture may be a negative electrode mixture or a positive electrode mixture, but the former is preferred.

[0044] The proportion of the electrode active material in the electrode mixture is, for example, 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. If the proportion of the electrode active material is too small, there is a possibility that sufficient energy density cannot be obtained. On the other hand, the proportion of the electrode active material is, for example, 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less. If the proportion of the electrode active material is too high, there is a possibility that the ionic conductivity and electronic conductivity of the electrode mixture are relatively reduced.

[0045] The electrode mixture contains at least one of a conductive material and a binder. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include rubber-based binders and fluoride-based binders.

[0046] The electrode mixture may further contain a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, and organic polymer electrolytes such as polymer electrolytes. Examples of the sulfide solid electrolyte include solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2. The electrode mixture may further contain a dispersion medium.

[0047] The electrode mixture can be prepared, for example, by mixing an electrode active material with at least one of a conductive material and a binder.

[0048] C.Battery Fig. 2 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 10 shown in Fig. 2 has a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the positive electrode layer 1 or the negative electrode layer 2 contains the electrode mixture described above in "B. Electrode mixture".

[0049] According to the present disclosure, by using the above-mentioned electrode mixture, a battery with small volume change due to charging and discharging is obtained. As described above, the electrode mixture may be a negative electrode mixture or a positive electrode mixture, but the former is preferable. Hereinafter, the details of the battery will be described in the case where the electrode mixture is a negative electrode mixture.

[0050] 1. Negative electrode layer The negative electrode layer in the present disclosure contains the above-mentioned electrode mixture (negative electrode mixture). The electrode mixture is the same as that described in "B. Electrode mixture" above, so the description here is omitted. The negative electrode layer may contain an electrolyte as necessary. The electrolyte is the same as that described in "3. Electrolyte layer". The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less, and may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less. In addition, as a method for forming the negative electrode layer, for example, a method of coating the electrode mixture (negative electrode mixture) on a negative electrode current collector can be mentioned.

[0051] 2. Positive electrode layer The positive electrode layer is a layer containing at least a positive electrode active material, and may contain at least one of an electrolyte, a conductive material, and a binder, as necessary.

[0052] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 , Li(Ni 0.5 Mn 1.5 )O4 and the like; and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0053] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because it can suppress the reaction between the oxide active material and a solid electrolyte (particularly a sulfide solid electrolyte). An example of the Li-ion conductive oxide is LiNbO3. The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less. In addition, for example, Li2S can be used as the positive electrode active material.

[0054] The electrolyte used in the positive electrode layer is the same as that described in "3. Electrolyte layer". The conductive material and binder used in the positive electrode layer are the same as those described in "B. Electrode mixture" above, so the description here is omitted. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less, and may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.

[0055] 3. Electrolyte layer The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution).

[0056] The solid electrolyte is the same as that described in "B. Electrode mixture" above, so the description here is omitted. On the other hand, the electrolyte preferably contains a supporting salt and a solvent. As the electrolyte, a known electrolyte can be used. The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less, and may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.

[0057] 4.Other configurations The battery in the present disclosure preferably has a positive electrode current collector that collects the positive electrode layer and a negative electrode current collector that collects the negative electrode layer. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon.

[0058] The battery of the present disclosure may further include a restraining tool that applies a restraining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, it is preferable to apply a restraining pressure in order to form a good ion conduction path and an electron conduction path. The restraining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the restraining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less.

[0059] 5.Battery The type of battery in the present disclosure is not particularly limited, but is typically a lithium ion battery. The battery in the present disclosure may be a liquid battery containing an electrolytic solution as an electrolyte layer, or may be an all-solid-state battery having a solid electrolyte layer as an electrolyte layer. The battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because it can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery.

[0060] Examples of applications of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery is preferably used as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), or as a power source for electrical appliances such as information processing devices. The method for producing the battery is not particularly limited, and known methods can be used.

[0061] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0062] [Example 1] In an Ar atmosphere, metallic Li and Si powder (manufactured by Kojundo Kagaku Co., Ltd., SIEPB32) were weighed out in a molar ratio of 4:1, mixed in a mortar for 1 hour, and Li 15 A Li-Si alloy with a Si4 phase was obtained. The obtained Li-Si alloy was reacted with ethanol under an Ar atmosphere. Then, acetic acid was added, and the liquid and solid components were separated by filtration. The separated solid component was vacuum dried at 120°C to obtain powdered porous Si.

[0063] The obtained porous Si and NaH, which is a Na source, were weighed out so that the molar ratio of NaH / porous Si was 1.1 / 1, and mixed using a cutter mill. The resulting mixture was placed in a reaction vessel and fired under conditions of Ar atmosphere at 475°C for 10 hours to obtain a Na-Si alloy.

[0064] The obtained Na-Si alloy was mixed with AlF3, which is a Na trapping agent. The AlF3 was classified using a sieve with a mesh size of 35 μm and a sieve with a mesh size of 75 μm. The obtained mixture was subjected to a first firing treatment under the conditions of an Ar atmosphere at 290°C for 10 hours, and then a second firing treatment was performed under the conditions of an Ar atmosphere at 340°C for 40 hours. The obtained compound was then put into an aqueous HNO3 solution with a concentration of 6% by weight and stirred for 1 hour. The stirred compound was then filtered, and the solid content was dried under the conditions of 120°C for 12 hours to obtain a powder.

[0065] The obtained powder and zinc chloride (ZnCl2) were weighed out so that the molar ratio of powder:ZnCl2 was 6:1, and mixed using a cutter mill. The obtained mixture was subjected to a third baking treatment under the conditions of an Ar atmosphere, 345°C, and 15 hours. The obtained compound was then put into an aqueous HNO3 solution with a concentration of 6% by weight and stirred for 1 hour. The stirred compound was then filtered, and the solid content was dried under the conditions of 120°C and 12 hours, to obtain a powder.

[0066] The obtained powder was put into a 3% by weight aqueous solution of hydrogen fluoride (HF) and stirred for 3 hours. The stirred compound was then suction filtered and the solid matter was dried at 120°C for 12 hours to obtain a powder. After drying, the obtained powder was put into acetone and coarse powder was removed using a resin sieve to obtain an electrode active material.

[0067] [Example 2] An electrode active material was obtained in the same manner as in Example 1, except that the second baking treatment was carried out under conditions of an Ar atmosphere, 340° C., and 80 hours.

[0068] [Example 3] An electrode active material was obtained in the same manner as in Example 1, except that the second baking treatment was carried out under conditions of an Ar atmosphere, 340° C., and 60 hours.

[0069] [Example 4] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere at 280° C. for 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere at 340° C. for 20 hours.

[0070] [Example 5] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere at 280° C. for 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere at 340° C. for 100 hours.

[0071] [Comparative Example 1] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere at 340° C. for 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere at 340° C. for 120 hours.

[0072] [Comparative Example 2] AlF3 was placed in a container together with crushing balls (φ1μm) and pulverized using a planetary ball mill (Fritsch) at 200 rpm for 3 hours. An electrode active material was obtained in the same manner as in Example 1, except that the pulverized AlF3 was used in the first firing treatment under conditions of an Ar atmosphere at 310°C for 10 hours, and the second firing treatment under conditions of an Ar atmosphere at 340°C for 10 hours.

[0073] [Comparative Example 3] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere at 360° C. for 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere at 360° C. for 100 hours.

[0074] [evaluation] (XRD measurement) X-ray diffraction (XRD) measurements using CuKα radiation were performed on the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3. As a result, it was confirmed that all of the electrode active materials had a silicon clathrate II type crystal phase as the main phase.

[0075] The intensity of peak A located near 2θ=20.09° in the silicon clathrate II crystal phase is I A The intensity of peak B located near 2θ = 31.72° is I B The maximum intensity at 2θ = 22° to 23° was defined as IM And, I A / I M and I B / I M As a result, the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 all had a I A / I M is greater than 1 and I B / I M was also greater than 1.

[0076] Using XRD analysis software (PDXL manufactured by RIGAKU), Rietveld analysis was performed, and a crystal model based on the atomic position information was created, and the distance between each atom in the crystal model was calculated. The maximum value of the diagonal length of the five-membered ring was taken as the five-membered ring size of the silicon clathrate II type crystal phase. The results are shown in Table 1. In addition, all of the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 had a small amount of diamond-type silicon crystal phase. The proportion of diamond-type silicon crystal phase (crystalline Si amount) was obtained using the results of the Rietveld analysis and the RIR method. The results are shown in Table 1.

[0077] (SEM observation) The average particle size (D 50 ) was obtained by observation with a scanning electron microscope (SEM). As a result, the average particle size D 50 Thus, the average particle size (D 50 ) is preferably 0.5 μm or more and 5 μm or less.

[0078] (Measurement of volume expansion rate) The electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were used as negative electrode active materials to fabricate all-solid-state batteries, respectively, by the following fabrication method.

[0079] (1) Preparation of the negative electrode The obtained electrode active material, sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of PVDF-based binder, and butyl butyrate were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a negative electrode current collector (Cu foil, manufactured by UACJ) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C. This resulted in a negative electrode having a negative electrode current collector and a negative electrode layer.

[0080] (2) Preparation of the positive electrode The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, average particle size 6μm), sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of PVDF-based binder, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with an ultrasonic dispersion device, and shaken for 3 minutes with a shaker. The coating was applied to a positive electrode collector (Al foil, manufactured by Showa Denko) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100 °C. This resulted in a positive electrode having a positive electrode collector and a positive electrode layer. The area of ​​the positive electrode was made smaller than that of the negative electrode.

[0081] (3) Preparation of solid electrolyte layer A sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a heptane solution containing 5% by weight of a butylene rubber-based binder, and heptane were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied onto a release sheet (Al foil) by the blade method using an applicator, and dried on a hot plate at 100°C for 30 minutes. This resulted in a transfer member having a release sheet and a solid electrolyte layer.

[0082] (4) Fabrication of all-solid-state batteries A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the resultant was set in a roll press machine and pressed at 100 kN / cm and 165° C. This produced a first laminate.

[0083] Next, the negative electrode was set in a roll press machine and pressed at 60 kN / cm and 25°C. This resulted in a pressed negative electrode. Then, a solid electrolyte layer for bonding and a transfer member were arranged in order from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer on the transfer member were arranged so as to face each other. The obtained laminate was set in a planar uniaxial press machine and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. This resulted in a second laminate.

[0084] Next, the solid electrolyte layer for bonding in the first laminate and the solid electrolyte layer in the second laminate were arranged to face each other, and then set in a flat uniaxial press and pressed at 200 MPa and 120° C. for 1 minute to obtain an all-solid-state battery.

[0085] (5) Measurement of volume expansion rate The obtained all-solid-state battery was charged, and the volume expansion rate was measured. The test conditions were a confining pressure (constant size) of 5 MPa, charging at 0.1 C, and a cut voltage of 4.55 V. The confining pressure at 4.55 V was measured, and the increase in the confining pressure from the state before charging was calculated, and the volume expansion rate was calculated. The results are shown in Table 1 and FIG. 3. The volume expansion rate results in Table 1 and FIG. 3 are relative values ​​when the result of Comparative Example 1 is set to 100.

[0086] [Table 1]

[0087] As shown in Table 1, the amount of crystalline Si was similar in Example 3 and Comparative Example 1, but there was a large difference in the volume expansion coefficient. Also, as shown in Table 1 and Fig. 3, it was confirmed that Examples 1 to 5 had a smaller volume expansion coefficient than Comparative Examples 1 to 3. In this way, the volume expansion coefficient was reduced by having the five-membered ring size fall within a predetermined range. [Explanation of symbols]

[0088] 1 ... Positive electrode layer 2 ... Negative electrode layer 3...electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...battery

Claims

1. An electrode active material having a silicon clathrate II type crystalline phase, The electrode active material, wherein the five-membered ring size in the crystal phase is 3.752 Å or more and 3.780 Å or less.

2. The electrode active material according to claim 1 , wherein the electrode active material has voids inside primary particles.

3. An electrode mixture comprising the electrode active material according to claim 1 or 2, and at least one of a conductive material and a binder.

4. A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery, wherein the positive electrode layer or the negative electrode layer contains the electrode mixture according to claim 3 .

5. The battery of claim 4 , wherein the electrolyte layer comprises a solid electrolyte.

Citation Information

Patent Citations

  • Active material, negative electrode layer, battery and these manufacturing methods

    JP2021158004A

  • Method for manufacturing negative electrode active material

    JP2023043948A